2008
DOI: 10.1007/s10534-008-9135-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency, thermodynamic and kinetic stability of marketed gadolinium chelates and their possible clinical consequences: a critical review

Abstract: Gadolinium-based contrast agents are widely used to enhance image contrast in magnetic resonance imaging (MRI) procedures. Over recent years, there has been a renewed interest in the physicochemical properties of gadolinium chelates used as contrast agents for MRI procedures, as it has been suggested that dechelation of these molecules could be involved in the mechanism of a recently described disease, namely nephrogenic systemic fibrosis (NSF). The aim of this paper is to discuss the structure-physicochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
375
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(393 citation statements)
references
References 93 publications
13
375
3
2
Order By: Relevance
“…6. Stability constants are more similar when the constant reflects a more physiological pH (36,37). Table 2 shows the conditional stability constants (K cond ), which reflect the calculated stability at a pH of 7.4.…”
Section: The Phagocytosis Of Gd Triggers Inflammatorymentioning
confidence: 99%
“…6. Stability constants are more similar when the constant reflects a more physiological pH (36,37). Table 2 shows the conditional stability constants (K cond ), which reflect the calculated stability at a pH of 7.4.…”
Section: The Phagocytosis Of Gd Triggers Inflammatorymentioning
confidence: 99%
“…This represents 96% of the 163 unconfounded cases where documentation showed that a single type of gadolinium-chelate was given to the patient before the onset of NSF; excluding cases where the type of agent was unknown, multiple types of agents were given, or there was no documentation of gadolinium-chelate administration. Gadodiamide (Omniscan) has relatively lower conditional stability (35,36). Normal half-life is approximately 90 min, but this can be prolonged to greater than 50 hours in the setting of renal failure.…”
Section: Gadolinium Agent Utilization and Safetymentioning
confidence: 99%
“…Furthermore, GC can be either nonionic (in which the number of carboxyl groups are reduced to three, which neutralize the three positive charges of Gd 3þ ) (strictly speaking, such GC are ''neutral'' rather than ''nonionic'') or ionic (in which the remaining carboxyl groups are salified with meglumine or sodium) (9,10,23,24) (Fig. 1).…”
Section: Chemistry and Pharmacology Of Gadolinium Chelatesmentioning
confidence: 99%
“…Such excipients are intended to ensure the absence of free Gd 3þ cations in pharmaceutical solutions for the duration of their shelf lives (23,24). According to the law of mass action (Eqs.…”
Section: Chemistry and Pharmacology Of Gadolinium Chelatesmentioning
confidence: 99%
See 1 more Smart Citation